Thermal Modification of Nanoscale Mask Openings in Polystyrene Sphere Layers. Issue 1663 (13th March 2014) - Riedl, Thomas; Strake, Matthias; Sievers, Werner; Lindner, Joerg K.N.
ABSTRACT: An experimental analysis of the morphology changes of hexagonally close packed polystyrene sphere monolayers induced by annealing in air is presented. The triangular interstices between each triple of spheres, which are frequently used as nanoscale mask openings in colloidal lithography, are observed to gradually shrink in size and change in shape upon annealing. Top view scanning electron microscopy images reveal that different stages are involved in the closure of monolayer interstices at annealing temperatures in the range between 110°C and 120°C. In the early stages shrinkage of the triangular interstices is dominated by material transport to and thus shortening of their corners, in the late stages interstice area reduction via displacement of the triangle edges becomes significant. At intermediate annealing times the rate of interstice area reduction displays a maximum before a stabilized state characterized by a rounded isosceles triangular shape forms.